24. Clinical outcomes and risk factors for mortality in diabetic patients with staphylococcus aureus pneumonia: A case-control study - Thu, Vo Pham Minh; Quyen, Nguyen Thuy; Dang, Tran Cong; Bao, Nguyen The (Tạp chí Nghiên cứu Y học, 2024)
The study was conducted to investigate the clinical outcomes and mortality risk factors related to Staphylococcus aureus pneumonia in patients with and without diabetes mellitus (DM). This was a case-control study on 118 patients with S. aureus pneumonia hospitalized between April 2021 and May 2023. The results reveal that diabetic female patients were prone to acquire Staphylococcus aureus pneumonia than non DM group (66.7% vs. 36.6%, p = 0.003); DM patients have more comorbidities (4.64 ± 2.07 vs. 3.46 ± 1.85; p = 0.003) compared to non-DM patients. Clinical outcomes, including 30-day all-cause mortality and pneumonia-related complications, showed no significant difference between patients with and without DM (all p > 0.05). Two independent risk factors for mortality in DM patients with S. aureus pneumonia are age > 65 (OR = 0.09, 95%CI: 0.01-0.64, p = 0.017) and central nervous system disease (OR = 18.54, 95%CI: 1.81-190.07, p = 0.014). The relatively high mortality rate in DM patients, predominantly attributed to MRSA infection, underscores the importance of staying focus on the diagnosis and adopting an appropriate initial antibiotic treatment approach. It is crucial to particularly note individuals with multiple comorbidities, especially those with central nervous system diseases.